AN ASSESSMENT ON COHERENCE AND GRAMMATICAL STRUCTURE OF STUDENTS’ WRITING SKILLS - Qurinta Shinta (Bajang Institute, 2021)
This study is aiming at assessing students’ competency in writing skill at First Semester Public Health Students of Diponegoro University. The target population were 25 Public Health students taking English class. A writing test was conducted to asses the students coherence, grammar, and sentence structure. This descriptive qualitative study is to discover (1) students’ awareness of applying transition signals devices to connect ideas (conjunction words, substitution, reference and ellipsis to create coherence. (2) students’ awareness in grammar and sentence structure. The result revealed that students found no problems using connective devices in their sentences. However, concerning grammar and sentence structure students faced difficulties in 1) Subject - Verb Agreement in which students often ignored plural forms, missed verbs, missed subjects in a sentence or they sometimes put two verbs in one sentence. 2) They were also still confused dealing with pronoun references. 3) Students also tend to write too long sentences without any punctuations.